Simpsonichthys nielseni sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the São Francisco River basin, Brazil - Costa, Wilson J.e.m. (Zootaxa, 2005)
Simpsonichthys nielseni, new species, is described from the middle São Francisco River basin, Brazil. It is a member of the S. notatus species group (which includes S. notatus, S. stellatus, S. similis, S. rufus, S. trilineatus, S. auratus, and S. radiosus), which is characterized by a derived pattern of frontal squamation. The new species differs from congeners by possessing a unique color pattern of the caudal fin in males, which includes six or seven light blue stripes diverging from the fin base, terminating in sharp tips on the fin margins. Simpsonichthys nielseni and S. stellatus share an apomorphic color pattern consisting of elongated light spots alternating with black zones on the dorsalfin base in males.